Comparative assessment of bone mineral density levels in type 2 diabetic subjects with or without chronic periodontitis: A cross-sectional study - Hira Ateeq; Afaf Zia; Qayyum Husain; Afshan Bey (Tabriz University of Medical Sciences, 2021)
Background. This cross-sectional study investigated the bone mineral density (BMD) in type 2 diabetes mellitus (T2DM) subjects with or without chronic periodontitis (CP). Methods. A total of 120 subjects aged 35‒55, divided equally into four groups: i) T2DM with CP, ii) T2DM without CP, iii) CP alone, and iv) healthy patients, were included in this study. Clinical parameters like plaque index (PI), gingival index (GI), and probing pocket depth (PPD) were recorded. All the participants were evaluated for blood sugar levels using glycated hemoglobin (HbA1c) and BMD by Hologic dual-energy x-ray absorptiometry (DEXA) scan. The association of BMD with clinical periodontal parameters and HbA1c in all groups was investigated using linear correlation analysis (r). Results. The mean value of BMD (0.9020±0.0952 g/cm2) was lower in subjects with both T2DM and CP compared to T2DM and CP alone. BMD was weakly correlated with all the clinical periodontal parameters; a positive correlation was observed between BMD and GI in the T2DM and CP group (r=0.405, P=0.026) and the CP group (r=0.324, P=0.081). A weak positive correlation was observed in BMD and HbA1c in the T2DM group (r=0.261, P=0.13), T2DM and CP group (r=0.007, P=0.970), with a negative correlation to HbA1c in the CP group (r= -0.134, P=0.479). Conclusions: Diabetes mellitus impacts clinical periodontal status and bone mass, and the effect is accentuated when chronic periodontitis is present. Based on the present study, BMD is associated with T2DM and CP, but a weak correlation was observed between BMD and HbA1c and clinical periodontal parameters.